Analysis of the spatial distribution and evolution of the number of contaminated areas in the hydrographic basins of the Aguapeí and Peixe Rivers (Research, Society and Development, 2021)
Contaminated site is defined as an area, land, location, installation or building that contains quantities or concentrations of matter, in conditions that cause or may cause damage to human health, the environment or other property to be protected. Seeking to obtain a better understanding of the contaminated sites in the hydrographic basins of the Aguapeí River and Peixe River (BHAP), the aim of this study was to survey the contaminated areas in the BHAP, identify the main potentially contaminating activities and the most affected physical environments, and simultaneously correlate the possible contamination values with the socioeconomic parameters of the respective cities. We selected contaminated sites data from cities belonging to the BHAP in the period from 2007 to 2019, obtained through the Contaminated and Rehabilitated Areas Reports of the State of São Paulo published by the Environmental Company of São Paulo State (CETESB). We identified 26 municipalities with contaminated sites, with gas stations being the main activity responsible for the contamination, while aromatic solvents and polycyclic aromatic hydrocarbons (PAHs) were the most reported contaminants. Groundwater and subsoil were, for the most part, the environments most impacted by contaminants. A strong correlation was found between the largest number of contaminants and cities with the largest area and largest number of inhabitants. In general, the identification of contaminated sites in hydrographic basins is an important tool that aims to assist in the management of contaminated areas and in the adoption of mitigation actions and the production of public policies aimed at mitigating the effects of contamination.